VALIDITAS RELIABILITAS INSTRUMENT TECHNOLOGYCAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) GURU SEKOLAH DASAR MUATAN PELAJARAN IPA - Anatri Desstya (AL-ASASIYYA: Journal Of Basic Education, 2018)
Measurement of teacher competence through TPACK is very important to do. However, the majority of the instruments used to measure TPACK for elementary school teachers are not yet in line with the needs of the 21st Century. This study aims to develop a TPACK instrument for elementary school teachers in a valid and reliable science lesson. This study uses the ADDIE model (Analysis, Define, Develop, Implementation, and Evaluation). The study sample involved 8 grade IV teachers from state and private elementary schools with A level of accreditation, spread across four sub-districts in the Surakarta region. Data analysis techniques use Pearson Correlation and Cronbach's Alpha. Research shows that there are 18 items that are declared valid and reliable. Valid is indicated by the Pearson Correlation value per question ranging from 0.504 - 0.904. Reliability is shown in the Cronbach's coefficient Alpha internal consistency value of 0.856. So that, overall, this instrument can be used to measure TPACK of elementary school teachers in the content of science lessons. This instrument can be used to map teacher competencies based on TPACK values. Furthermore, if there are some weaknesses in the 7 aspects of the TPACK, policy makers can determine the follow-up that needs to be determined to further improve the competence of elementary school teachers.